2022
DOI: 10.3390/genes13030508
|View full text |Cite
|
Sign up to set email alerts
|

2022 Overview of Metabolic Epilepsies

Abstract: Understanding the genetic architecture of metabolic epilepsies is of paramount importance, both to current clinical practice and for the identification of further research directions. The main goals of our study were to identify the scope of metabolic epilepsies and to investigate their clinical presentation, diagnostic approaches and treatments. The International Classification of Inherited Metabolic Disorders and IEMbase were used as a basis for the identification and classification of metabolic epilepsies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…However, metabolic epilepsies are more frequently associated with generalized seizures. [ 12 ] We observed that generalized seizures were the dominant semiology that occurred in nearly three-fourth of our cases. Multiple seizure types were noticed in one-third of cases (20/63) which provided a clue to metabolic etiology and further workup.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…However, metabolic epilepsies are more frequently associated with generalized seizures. [ 12 ] We observed that generalized seizures were the dominant semiology that occurred in nearly three-fourth of our cases. Multiple seizure types were noticed in one-third of cases (20/63) which provided a clue to metabolic etiology and further workup.…”
Section: Discussionmentioning
confidence: 76%
“…The prevalence of epilepsy among inherited metabolic disorders was found to be 40.4% (63/156) in our cohort, which is compatible with previous studies. [ 11 , 12 ] Youssef-Turki et al . [ 13 ] in a recent review have reported that 600 metabolic epilepsies have been identified, accounting for as much as 37% of all currently described inherited metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T A B L E 1 Biochemical analysis at different time of disease course of the superrefractory status epilepticus Indeed, metabolic epilepsies (epilepsies that results directly from an inherited metabolic disorder in which seizures are a core symptom of the disorder 1 ) are increasingly diagnosed, accounting for 25% of EEs of unknown etiology tested with WES. 20,21 Making a diagnosis of MCADD is crucial considering that a preventive nutritional support is necessary to achieve a good prognosis: Among patients not previously diagnosed, about 25% die during an acute episode of metabolic distress, while prognosis strongly improves after recognition of the enzyme defect. 22 Early identification of MCADD is even more important in patients with epilepsy, where diagnosis not only may reduce the burden of recurrent metabolic crises but also control seizures, prevent brain damage, and avoid development delay.…”
Section: Discussionmentioning
confidence: 99%
“…This single case report is paradigmatic of a lost generation of patients who remained undiagnosed for a long time, especially between the high number of EEs of unknown etiology. We advise adult epileptologists to consider IEMs in the diagnostic process of EEs, as early diagnosis and treatment may affect disease outcomes 20 . Indeed, metabolic epilepsies (epilepsies that results directly from an inherited metabolic disorder in which seizures are a core symptom of the disorder 1 ) are increasingly diagnosed, accounting for 25% of EEs of unknown etiology tested with WES 20,21 …”
Section: Discussionmentioning
confidence: 99%